2021
DOI: 10.3390/su13084119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physical, Chemical, and Environmental Properties of Biomass Bottom Ash for Use as a Filler in Bituminous Mixtures

Abstract: The road construction sector is one of the most raw material-intensive sectors in existence. As a result, it has a significant impact on the environment. For this reason, there are several research projects in which industrial by-products are used as raw materials. In turn, energy production from biomass combustion is considered to be one of the most promising energy sources. However, this type of energy produces a number of wastes that need to be treated, such as biomass bottom ash. This research evaluates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…The content of Cl − ranged from 15.7 to 63.2 mg/kg, and in the case of SO 4 2− , the differences were even greater, ranging from 1210 to 15,430 mg/kg. A high concentration of sulphur compounds (6.43 wt % and 3.3 wt %) in biomass bottom ash was also recorded by Suárez-Macías et al [23] and Link et al [21], respectively. These findings are perfectly in line with our results.…”
Section: So 4 2−supporting
confidence: 62%
See 3 more Smart Citations
“…The content of Cl − ranged from 15.7 to 63.2 mg/kg, and in the case of SO 4 2− , the differences were even greater, ranging from 1210 to 15,430 mg/kg. A high concentration of sulphur compounds (6.43 wt % and 3.3 wt %) in biomass bottom ash was also recorded by Suárez-Macías et al [23] and Link et al [21], respectively. These findings are perfectly in line with our results.…”
Section: So 4 2−supporting
confidence: 62%
“…Horák et al [19] obtained similar data for ashes after combusting various fractions of municipal waste, indicating that in the case of floor coverings mixed with dry beech, the content of chlorides may reach even up to 191,000 mg/kg. A high concentration of chlorine (4.7 wt %) in biomass bottom ash was also observed by Suárez-Macías et al [23] and Link et al [21]. In water extracts, the concentration of chloride was considerably lower and amounted to 134 mg/kg on average [23].…”
Section: supporting
confidence: 56%
See 2 more Smart Citations
“…The studies conducted so far [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have revealed that bio-ash considerably varies as to its composition and properties, depending on the origin of the biomass, biomass handling, and the combustion technology and temperature. The wide range of compositions and properties of bio-ash requires the testing of individual sources with the purpose of determining the possibility of using bio-ash in road construction as a substitute for traditional materials.…”
Section: Introductionmentioning
confidence: 99%